A Brief Study about Cerebral Palsy: Comorbidities and Second hidden Side - Desouza, Jinela; Patil, Mohan (Current Overview on Disease and Health Research Vol. 4, 2022)
The study aimed to assess the comorbidities in children suffering from Cerebral palsy (CP) in Kolhapur district, India. The cross-sectional study was conducted among children suffering from cerebral palsy and presenting to Department of Paediatrics (n=250), D. Y. Patil Medical College, between October 2018 to October 2019. Detailed history with clinical examination were recorded in a pre-designed performa. The patients were classified based on physiological and topographical factors. Common form of cerebral palsy was spasti Of the total participants (n=250), male predominance was observed (n=140); with age range of 1c type (n=140; 56%). Most common type among spastic CP was diplegia -18 years. (n=96; 38%). In spastic CP cases (n=65), children had speech abnormalities. All of the children with spastic hemiplegia (n=3) had intellectual disabilities. It is clear that the underlying co-morbidities are what actually cause the disability; the motor impairment is only the top-notch symptom.